La importación de leche en Colombia y sus efectos sobre el mercado interno (2007 – 2014) (2015)
Colombia´s government has shown during the last decade a special interest to join a wider commercial dynamic through Free Trade Agreements with many countries all over the world. This Free Trade Agreements have worried some economic sectors, just like the Colombian dairy sector. They have specifically said that those agreements mean its bankruptcy. However, the empiric evidence and data analysis discussed in this thesis does not support what Colombian dairy sector claims. Peculiarly, using a VAR model, under three different scenarios, and a structural change test, one cannot affirm that the Free Trade Agreements signed with the United States neither with the European Union, represent a reduction in the volume of purchases of raw milk to producers in Colombia, at least until December 2014.